SPE/ICoTA Coiled Tubing Roundtable 1998
DOI: 10.2118/46053-ms
|View full text |Cite
|
Sign up to set email alerts
|

Applications Update - Advanced Composite Coiled Tubing

Abstract: Composite Spoolable Pipe for use in the Oil and Gas Industry is a new emerging technology. Enabling benefits include increased corrosion resistance, major weight reduction over steel as well as increased fatigue resistance. One company is close to commercial introduction of composite spoolable pipe for both well servicing and well completion operations. This paper will detail the latest application developments achieved at the time of the conference. It will cover the advancements made since the last update, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thermosetting flexible tube, [21][22][23][24][25] as typified by the Fiberspar products shown in Fig. 9, was first developed in response to the need for a non-metallic replacement for steel coil tubing.…”
Section: Spoolable Thermosetting Tubementioning
confidence: 99%
“…Thermosetting flexible tube, [21][22][23][24][25] as typified by the Fiberspar products shown in Fig. 9, was first developed in response to the need for a non-metallic replacement for steel coil tubing.…”
Section: Spoolable Thermosetting Tubementioning
confidence: 99%
“…14 The most important advantages of composite over the conventional steel are light weight, corrosion and fatigue resistance, high stiffness and strength, and design flexibility. 18 Composite material properties can be converted into important financial and performance benefits during offshore operations. Studies have shown that the use of composite products can reduce offshore capital requirements, decrease maintenance costs, and enable operations that otherwise are not feasible both technically and financially.…”
Section: Benefits Of Composite Materialsmentioning
confidence: 99%
“…The earlier mentioned definition or characteristics of composites that make them ideal candidates for oilfield application include resistance to chemical and cathodic corrosion, high strength, light weight, and flexibility. 18 Generally speaking, composites have a higher strength-to-weight ratio than steel. With the ability to control the type, amount, and direction of application of the reinforcement material, composite materials become an ideal candidate for widely varying pressure applications.…”
Section: Composite Materials Properties and Compositionmentioning
confidence: 99%